THE FORMATION OF THE SANTO DIAS NO CEDEM FUND; CONSTRUCTION OF THE MEMORY OF THE OPERATOR MARITAL - Nogueira Diniz, Carlos Alberto [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2019)
This paper aims to analyze part of the worker's memory construction process Santo Dias da Silva since the incorporation of the Fund Santo Dias collection located in the Center of Memory and Documentation of UNESP (CEDEM). The Santo Dias Fund is one of the fewest collections in Brazil dedicated to the memory of a single worker. This collection was in part formed by documents granted by the family, friends and militant companions of the social pastoralists and unions. Although the worker's memory size Santo Dias is much larger than the collection and it is present in other mnemonic manifestations, the institutionalization of this documentation was very important for the study and maintenance of the memory of social movements in Brazil.
Keywords: Silva; Santo Dias da; 1942-1979; Collective memory; Social movements; Syndicalism